A stochastic model of the single photon response in Drosophila photoreceptors - Nikolic,K; Loizu,J; Degenaar,P; Toumazou,C (Integrative Biology, 2010)
We present a quantitative model for the phototransduction cascade in Drosophila photoreceptors. The process consists of four stages: (1) light absorption by Rhodopsin, (2) signal amplification phase mediated by a G-protein coupled cascade, (3) close/open state kinetics of the transient receptor potential (TRP) ion channels which regulate the ionic current in/out of the cell and (4) Ca regulated positive and negative feedbacks.The model successfully reproduces the experimental results for: single photon absorption "quantum bump" (QB), statistical features for QB (average shape, peak current average value and variance, the latency distribution, etc), arrestin mutant behaviour, low extracellular Ca2+ cases, etc. The TRP channel activity is modeled by a Monod-Wyman-Changeux (MWC) model for allosteric interaction, instead of using the usual ad hoc Hill equation. This approach allows for a plausible physical explanation how Ca/calmodulin regulate the protein activity. The cooperative nature of the TRP channel activation leads to "dark current" suppression at the output allowing for reliable detection of a single photon. Stochastic simulations were produced by using the standard rate equations combined with the Poisson distribution for generating random events from the forward and the reverse reaction rates. Noise is inherent to the system but appears to be crucial for producing such reliable responses in this complex, highly nonlinear system. The approach presented here may serve as a useful example how to treat complex cellular mechanisms underlying sensory processes.